MR elastography for noninvasive assessment of hepatic fibrosis: Reproducibility of the examination and reproducibility and repeatability of the liver stiffness value measurement. Issue 2 (15th April 2013) - Lee, Ye ji; Lee, Jeong Min; Lee, Jeong Eun; Lee, Kyung Bun; Lee, Eun Sun; Yoon, Jeong‐Hee; Yu, Mi Hye; Baek, Jee Hyun; Shin, Cheong Il; Han, Joon Koo; Choi, Byung Ihn
Abstract : Purpose: To determine the reproducibility of MR elastography (MRE) and the reproducibility and repeatability of the stiffness measurement of MRE in the staging of liver fibrosis. Materials and Methods: Ninety‐four patients, who underwent liver MRE, were included in this study. The patients were classified into group 1 (n = 47) and group 2 (n = 47) according to our knowledge of their histologic hepatic fibrosis (HF) stage. To analyze the reproducibility of MRE, the group 1 patients underwent MRE twice. In addition, to evaluate the repeatability and reproducibility of the stiffness measurement of MRE, a single observer measured the stiffness values of the second MREs in group 1 twice, and two observers independently measured the stiffness values of MRE in group 2. A 95% Bland‐Altman limits of agreement and intraclass correlation coefficients (ICCs) were used to evaluate the reproducibility and repeatability of MRE. Results: In group I, there was no significant difference in the mean liver stiffness values of the first and second MRE examinations, i.e., 3.45 ± 0.25 kPa vs. 3.35 ± 0.23 kPa (p = 0.22). The reproducibility of the MRE examination and the reproducibility and repeatability of the stiffness measurement were high, i.e., the ICCs of each parameter were 0.945, 0.827, and 0.963, respectively, and the 95% limits of agreement were 25.3%, 35.35%, and 18.0%, respectively. Conclusion: MRE is a promising tool for evaluating HF and has high reproducibility of the examination as well as reproducibility and repeatability of the stiffness measurements.J. Magn. Reson. Imaging 2014;39:326–331 . ©2013 Wiley Periodicals, Inc .